Tantangan dan Strategi Pengembangan Profesionalisme Tenaga Pendidik di Era Digital di SMKN 1 Surabaya - Alvian, Aqilla Rizki; Rowiari, Destri Natalia; Windasari, Windasari; Cindy, Agustin Hanifa (Lembaga Yasin AlSys, 2024)
The challenges faced by teachers in maintaining and improving their professionalism in the digital era, especially at SMKN 1 Surabaya. The digital era has changed the role of teachers, and they must adapt to new methods in the teaching and learning process. One of the main challenges is the need for teachers to master digital technology in the learning process. Students are used to the digital world, and teachers must be able to use various digital platforms and media effectively. In addition, teachers must help students to distinguish and use information wisely amidst the overwhelming flow of information online. This paper also describes the strategies used by SMKN 1 Surabaya to develop the professionalism of its teachers, such as regular training and workshops on digital teaching tools and collaboration with external parties to provide resources and facilitators. The research method used is qualitative descriptive analysis, which focuses on an in-depth study of the subject, with a systematic and comprehensive explanation of the facts found in the field. The research was conducted on March 7, 2024, at SMKN 1 Surabaya, and data was collected through a structured questionnaire with the school accountant. The research findings show that SMKN 1 Surabaya faces considerable challenges in maintaining and improving the professionalism of its teachers in the digital era, but the school has implemented various strategies to overcome these challenges.